Resolving the structure and dynamics of the disordered C terminus of human cardiac troponin T and effects of cardiomyopathic mutations - Garrett S. Crosby; Bai Hei; Melissa L. Lynn; Ananya Chakraborti; Steven D. Schwartz; Jil C. Tardiff (Proceedings of the National Academy of Sciences, 2025)
The C-terminal tail of cardiac troponin T (C-cTnT) inhibits thin filament activation and is a hotspot for cardiomyopathic mutations and variants. The mechanism whereby this region limits activation is not well understood. The last 16 C-terminal residues form a highly flexible and disordered domain and thus have been poorly resolved in studies to date. Using Time-Resolved fluorescence resonance energy transfer (TR-FRET) we resolved the structure of the disordered C-cTnT and studied the structural and dynamic effects of cardiomyopathic mutations on the region. For wildtype (WT) thin filaments, our data revealed a repositioning of cTnT-274 closer to cTnC when bound with calcium and myosin, while cTnT-283 did not move relative to cTnC. Myosin binding decreased the flexibility of cTnT-274 while having no effect on cTnT-283. We found that hypertrophic cardiomyopathy mutation cTnT-K273E decreased flexibility and placed the C-cTnT in an activated position in the blocked and closed states, resulting in increased actomyosin interactions in the absence of calcium; while dilated cardiomyopathy mutation cTnT-D270N increased flexibility and decreased the ability of the C-cTnT to reach its activated position in the open state but had no effect on actomyosin interactions. Our results demonstrate the WT C-cTnT undergoes a disordered to ordered transition upon myosin binding that is directly altered in the presence of cardiomyopathic mutations. These data provide a structural framework for the coupling of TR-FRET with high-resolution molecular dynamics as a tool for interrogating intermolecular interactions of intrinsically disordered proteins and protein complexes.